Journal of a second voyage for the discovery of a north-west passage from the Atlantic to the Pacific [electronic resource] : performed in the years 1821-22-23, in His Majesty's ships Fury and Hecla, under the orders of Captain William Edward Parry, R.N., F.R.S., and commander of the expedition. - Parry, William Edward, Sir, 1790-1855. (London : J. Murray, 1824)
Vol. I. Tables. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 39788-39790. "Published by authority of the Lords Commissioners of the Admiralty." "Illustrated by numerous plates." Electronic reproduction. Mode of access: Internet. 44